Prediction of common hepatic artery catheter insertion based on celiac trunk morphology - Atsushi Saiga; Hajime Yokota; Akira Akutsu; Yoshihiko Ooka; Yoshihiro Kubota; Takeshi Wada; Jun Koizumi; Takashi Uno (Diagnostic and Interventional Radiology, 2023)

(untitled)
PURPOSEThis study aimed to predict the ability to insert a 4–5 French (Fr) catheter insertion with a guidewire into the common hepatic artery (CHA) based on celiac trunk morphology.METHODSThis retrospective study included 64 patients who underwent balloon-occluded transcatheter arterial chemoembolization (n = 56), transcatheter arterial chemotherapy (n = 2), or were fitted with an implantable port system (n = 6) between June 2019 and December 2019 in our institution. The morphology of the celiac trunk was classified into three types (upward, horizontal, and downward) based on celiac angiography. The aortic–celiac trunk angle was measured on sagittal images of preprocedural contrast-enhanced computed tomography (CT). We reviewed whether a 4–5-Fr shepherd’s hook catheter could advance beyond the CHA using a 0.035-inch guidewire (Radifocus® Guidewire M; Terumo). Three patients were diagnosed with median arcuate ligament syndrome (MALS) based on the characteristic hook shape of the celiac artery on sagittal images of contrast-enhanced CT. The predictive ability of celiac angiography and preprocedural CT for CHA insertion success was evaluated. In unsuccessful cases, the balloon anchor technique (BAT) was attempted as follows: (1) a 2.7/2.8-Fr microballoon catheter (Attendant Delta; Terumo) was placed beyond the proper hepatic artery, and (2) the balloon was inflated as an anchor for parent catheter advancement.RESULTSUpward, horizontal, and downward celiac trunk types were noted in 42, 9, and 13 patients, respectively. The median CT angle was 122.83° (first quartile–third quartile, 102.88°–136.55°). Insertion in the CHA using the guidewire was successful in 56 of 64 patients (87.50%), and the success rate in the downward type was significantly lower than that in the upward type [42/42 (100%) vs. 7/13 (53.85%), P < 0.001]. The CT angle was significantly larger downward in the unsuccessful group than in the successful group (121.03° vs. 140.70°, P = 0.043). Celiac angiography had a significantly higher area under the curve (AUC) than preprocedural CT (AUC = 0.91 vs. AUC = 0.72, P = 0.040). All three cases of MALS showed unsuccessful CHA insertion. In all eight patients with unsuccessful insertion, the catheter could be advanced using the BAT [8/8 (100%)].CONCLUSIONCeliac angiography and preprocedural CT could predict CHA catheter insertion using a guidewire, and celiac angiography had high predictability. CT could detect MALS, a risk factor for unsuccessful CHA insertion.